Phase I clinical trial of a novel procaspase-3 activator SM-1 with temozolomide in recurrent high-grade gliomas - Mengqian Huang; Zhuang Kang; Shenglan Li; Botao Zhang; Yantao Xiao; Shangwei Li; Wenbin Li (Neoplasia: An International Journal for Oncology Research)
Objective: Despite a standard of care, the mortality of recurrent high-grade gliomas (HGGs) remains high. SM-1 is a novel molecular activator that has shown to target procaspase-3, which is overexpressed in HGGs. A phase I clinical trial was conducted to evaluate the safety, pharmacokinetics, and primary clinical efficacy of SM-1 plus TMZ. Participants received escalating doses of daily oral SM-1 (450, 600, and 800 mg) plus standard TMZ therapy. Methods: In the preclinical study, the synergistic effects of SM-1 and temozolomide (TMZ) in rodent models were evaluated. In the clinical study, adult patients received SM-1 therapy in various doses in combination with a standard TMZ dosing. The tolerability and pharmacokinetics data of the combination therapy were tested. The primary efficacy was measured by tumor response in accordance with the RANO criteria. Results: A total of 13 patients with recurrent HGG were enrolled, with 11 patients completed ≥ two cycles of therapy and received tumor assessment. Among them, one patient had complete response, whereas two patients had partial response for the best change from baseline. No dose-limited toxicities were observed, and no maximum tolerated dose was reached. Conclusion: SM-1 has the potential to enhance antitumor activity while alleviating the side effects of TMZ. SM-1 exhibited mild toxicity in patients with recurrent HGG. The combination of SM-1 and TMZ warrants further investigation, with promising clinical outcomes. The monotherapy phase and expansion phase of SM-1 are still ongoing. (ClinicalTrials.gov number, CTR20221641).